Efectos del bloque de constitucionalidad en materia de prescripción de la acción penal en Colombia (2009)
In Colombia, the articles 93, 94 and 214 of the Constitutional Charter create a bridge of implementation through the International Law of Human Rights and International Humanitarian Law are integrated into the Colombian law under the figure of the Constitutional Bloc . The main effect of this is to adapt the internal law to the international obligations of the State, and consequently, the evolution in the protection and guarantee of human rights domestically.However, the implementation process can generate complex problems that arise, for example, the contradictions between the rules of law which are based on legal principles rooted in the country and the bloc of of constitutionality’s rules. The case of prescription of prosecution in Colombia is a complex case, but international norms is evident in the existence of a rule on the applicability of prosecution of war crimes and crimes against humanity. This article is the conclusion of a balance of the principles found there